2022
DOI: 10.1002/nbm.4719
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and physiologic magnetic resonance imaging in distinguishing true progression from pseudoprogression in patients with glioblastoma

Abstract: Pseudoprogression (PsP) refers to treatment-related clinico-radiologic changes mimicking true progression (TP) that occurs in patients with glioblastoma (GBM), predominantly within the first 6 months after the completion of surgery and concurrent chemoradiation therapy (CCRT) with temozolomide. Accurate differentiation of TP from PsP is essential for making informed decisions on appropriate therapeutic intervention as well as for prognostication of these patients. Conventional neuroimaging findings are often e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 162 publications
0
13
0
Order By: Relevance
“…PsP is predominantly a subacute treatment-related reaction that may or may not involve neurological deterioration [ 4 ]. Radiologically, PsP can be described as new or enlarging areas of contrast enhancement on follow-up MRI within the first 3–6 months of the completion of chemoradiotherapy following surgical resection, which subsides or stabilizes without further intervention treatments, and some studies suggest that PsP may have a relatively good prognosis [ 7 , 8 ]. Various reports have defined the time of PsP occurrence differently, which is likely to affect the incidence.…”
Section: Characteristics Of Trcsmentioning
confidence: 99%
See 1 more Smart Citation
“…PsP is predominantly a subacute treatment-related reaction that may or may not involve neurological deterioration [ 4 ]. Radiologically, PsP can be described as new or enlarging areas of contrast enhancement on follow-up MRI within the first 3–6 months of the completion of chemoradiotherapy following surgical resection, which subsides or stabilizes without further intervention treatments, and some studies suggest that PsP may have a relatively good prognosis [ 7 , 8 ]. Various reports have defined the time of PsP occurrence differently, which is likely to affect the incidence.…”
Section: Characteristics Of Trcsmentioning
confidence: 99%
“…The O 6 -methylguanine-DNA methyltransferase (MGMT) status [ 9 ], isocitrate dehydrogenase (IDH) gene status [ 11 ], Ki67 expression [ 12 ], and p53 status [ 13 ] were all associated with PsP occurrence. Tumors with a methylated MGMT promoter and IDH mutation show PsP more frequently and have better median OS [ 7 , 9 ], and a study found a 91.3% probability of PsP in patients with methylated MGMT promoter tumors [ 9 ]. These biomarkers clearly affect PsP incidence and prognosis.…”
Section: Characteristics Of Trcsmentioning
confidence: 99%
“…32 Alternatively, radiomics analysis is capable of converting images into quantitative and objective features. Multiple radiomics studies have demonstrated that such quantitative measurements have potential in the diagnosis and subsequent management of patients with gliomas, [33][34][35][36][37][38][39][40][41][42] including APTw-based radiomics studies for the molecular marker identification 43 and differentiation of gliomas from metastases. 44 In addition, researchers are beginning to develop computer-aided diagnostic models for radiomics analysis to assess the treatment response of gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed to be due to factors causing tissue inflammation and the upregulation of vascular endothelial growth factor (VEGF), which lead to increased vessel permeability and edema. Patients exhibiting pseudoprogression show a favorable response to temozolomide chemotherapy treatment [9] and are symptomatically managed along with follow-up CE-MRI scans.…”
Section: Introductionmentioning
confidence: 99%